Whole-genome sequencing of an acidophilic Rhodotorula sp. ZM1 and its phenol-degrading capability under acidic conditions. (October 2019) - Su, Xiaomei; Zhou, Meng; Hu, Pin; Xiao, Yeyuan; Wang, Zhen; Mei, Rongwu; Hashmi, Muhammad Zaffar; Lin, Hongjun; Chen, Jianrong; Sun, Faqian
Abstract: The goal of this work was to investigate the genetics of an acidophilic phenol-degrading yeast strain using whole-genome sequencing (WGS), characterize the growth of the strain and phenol degradation capability as well as degradation pathway under extremely acidic conditions. The result showed that the strain ZM1 isolated from an acid mine drainage (AMD) belongs to basidiomycetous yeast Rhodotorula sp., which possesses some unique genes compared to other four closely related Rhodotorula species. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis suggested that ZM1 possessed the degradation potentials for aromatic compounds. ZM1 was acidophilic with the optimum growth at the initial pH of 3.0. It could adjust pH to desired levels probably by acid production during the cultivation. Notably, at pH 3.0, the strain ZM1 showed a high phenol-degrading capability that almost completely degraded 1100 mg/L of phenol in 120 h with the highest degradation rate of 0.074 g/(g cell dry weight h). Under the same pH, the strain could completely degrade 500 mg/L phenol within 48 h at NaCl concentration up to 10 g/L. The identification of the gene catA by the KEGG analysis, together with the presence of metabolic intermediate of cis, cis- muconic acid detected by gas chromatography-mass spectrometry, confirmed that the strain ZM1 degraded phenol via ortho- cleavage pathway. These findings suggest that the indigenous yeasts strain ZM1 could be exploited as an important member for in-situ biodegradation of aromatic compounds in the extremely acidic environments. Graphical abstract: Image 1 Highlights: Strain ZM1 was isolated from acid mine drainage and WGS was performed. ZM1 possesses some unique genes compared to 4 closely related Rhodotorula species. Rhodotorula sp. ZM1 was acidophilic and could self-adjust pH to desired levels. ZM1 degrade 1100 mg/L phenol in 120 h up to the rate of 0.074 g/(g CDW h) at pH 3.0. The strain ZM1 with salinity resistance degraded phenol via ortho- cleavage pathway.